Clinical and Radiographic Success of Selective Caries Removal to Firm Dentin in Primary Teeth: 18-Month Follow-Up. (26th March 2018) - Stafuzza, Tássia Carina; Vitor, Luciana Lourenço Ribeiro; Rios, Daniela; Cruvinel Silva, Thiago; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
Abstract : The selective caries removal is increasingly spreading in daily clinical practice because this minimally invasive technique treats deep carious lesion and decreases the risk of pulp exposure. This case report was aimed at describing the selective removal to firm dentin on the primary mandibular left first molar of a girl aged 7 years and 6 months. The Mineral Trioxide Aggregate (MTA Angelus™) was used as liner, and the tooth was definitively restored with resin-modified glass ionomer cement (Vitremer™). The clinical and radiographic following-up was performed at 6, 12, and 18 months after treatment. The treatment showed satisfactory results after 18-month following-up, suggesting that this minimally invasive approach for carious lesion removal can replace the total removal, when properly indicated. Notwithstanding, further randomized clinical trials with longer following-up periods are still necessary.